PERTUMBUHAN DAN PRODUKSI KACANG TANAH DENGAN PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT PADA FREKUENSI PEMBUMBUNAN YANG BERBEDA - Michael Sembiring; Rosita Sipayung; Ferry E. Sitepu (Jurnal Agroekoteknologi, 2014)
Peanut is one of food plant that has high economical value because of its nutrient content especially proteinand fat. The other alternative to increase peanut productivity were application of empty fruit bunch compostand pile up frequency. The purpose of this study was to determine the effect of empty fruit bunch compostand pile up frequency toward the growth and production of peanut This research was held on JalanPenampungan, Delitua, Namorambe, Deli Serdang with altitude ± 25 metre,took place on April to July 2013. The study design was a factorial randomized block design with two factors, namely empty palm bunches (0,12, 24 and 36 g /plant) and pile up frequency (0; 21; 21,42 and 21,42,63 days). The parameters measuredwere plant height, number of branches, days to flowering, number of ginofor per sample, number of pods persample, number of pods per plot, weight of pods per sample, the weight of pods per plot, seed weight persample, dry weight of 100 seeds. The results showed that composting of empty palm bunches significantlyaffect the parameters of number of ginofors per sample. Pile up frequency significantly affected the numberof pods per plot. Treatment interaction significantly affected the number of ginofors per sample.Keywords: peanut, empty palm bunches, pile up frequency.